A high-resolution lithospheric magnetic field model of China and surroundings by using CHAMP, Swarm, CSES-1, and MSS-1 satellite magnetic measurements and aeromagnetic anomaly data - Pan Zhang; JinSong Du; Liang Yin; Qing Yan; JiaXuan Zhang; HouPu Li; Keke Zhang; Chao Chen (Earth and Planetary Physics)
The CUG_CLMFM3D series comprises high-resolution three-dimensional lithospheric magnetic field models for China and its surroundings. The first version, CUG_CLMFM3Dv1, is a spherical cap harmonic model integrating the WDMAMv2 (World Digital Magnetic Anomaly Map version 2) global magnetic anomaly grid and nearly a decade of CHAMP (Challenging Minisatellite Payload for Geophysical Research and Application) satellite vector data. It achieves a ~5.7 km resolution but has limitations: the WDMAMv2 grid lacks high-resolution data in the southern Xinjiang and Tibet regions, which leads to missing small- to medium-scale anomalies, and unfiltered CHAMP data introduce low-frequency conflicts with global spherical harmonic models. Above the altitude of 150 km, correlations with global models drop below 0.9. The second version, CUG_CLMFM3Dv2, addresses these issues by incorporating 5-km-resolution aeromagnetic data and rigorously processed satellite data from CHAMP, Swarm, CSES-1 (China Seismo-Electromagnetic Satellite 1), and MSS-1 (Macau Science Satellite 1). The comparison analysis shows that the CUG_CLMFM3Dv2 captures finer high-frequency details and more stable long-wavelength signals, offering improved magnetic anomaly maps for further geological and geophysical studies.